Respuesta :

Elimination is getting rid of one of the variables the answer is (-6,-7)
Ver imagen Myles21

Answer:

x = -6    y = -7

Step-by-step explanation:

multiply the 2nd equation by -1 to get 2x + y = -19

Now  -2x + 4y = -16

         2x+y = -19

               5y = -35

                 y = -7

Substitute y = -7 into the second equation to get -2x + 7 = 19

                                                                                 -2x = 12

                                                                                    x = -6

Check:  Substitute values into the 1st equation

             -2(-6) +4(-7) = 12 - 28 = -16  

So we have the correct values for x and y